2021
DOI: 10.1097/mpg.0000000000003280
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Lubiprostone in Pediatric Patients With Functional Constipation

Abstract: Objectives: Pediatric functional constipation (PFC) affects up to 30% of children. Current treatments often do not sustain symptomatic relief. Lubiprostone is a locally acting chloride channel activator that promotes fluid secretion into the small bowel without affecting serum electrolyte concentrations. We assessed the safety/tolerability of oral lubiprostone as treatment for PFC in a 24-week study. Methods: This phase 3 open-label safety trial conducted from April-Nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
3
6
0
1
Order By: Relevance
“…Another multicenter open-label trial investigated the safety of lubiprostone in children with FC aged 6–17 years (mean age 10.3 years). In line with the other trials, the drug was well tolerated in children [ 83 ]. Side effects of lubiprostone are generally minor and include nausea, vomiting, abdominal pain, and diarrhea [ 82 ].…”
Section: Novel Therapiessupporting
confidence: 79%
See 1 more Smart Citation
“…Another multicenter open-label trial investigated the safety of lubiprostone in children with FC aged 6–17 years (mean age 10.3 years). In line with the other trials, the drug was well tolerated in children [ 83 ]. Side effects of lubiprostone are generally minor and include nausea, vomiting, abdominal pain, and diarrhea [ 82 ].…”
Section: Novel Therapiessupporting
confidence: 79%
“…Children were allocated to a dosage of 12 µg once a day, 12 µg twice a day, or 24 µg once a day, depending on their weight. None of the studies reported any difference between the dosages for efficacy and safety [81][82][83].…”
Section: Prosecretory Agentsmentioning
confidence: 99%
“…However, data regarding its role in childhood and pediatric patients are limited. [10][11][12] The current study showed that lubiprostone was superior to conventional laxatives in terms of improving SBM and BSF. In the current study, the clinical response was significantly higher in the lubiprostone group (91.4%) than in the conventional laxatives group (34.3%).…”
Section: Discussionmentioning
confidence: 61%
“…Upper abdominal pain was the only TRAE leading to discontinuation (of 12 patients in total) that occurred in >1 patient. 12 Diarrhea and vomiting were the most frequent (≥3% of patients). They reported no difference between different doses of lubiprostone as regards TARE.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Серед функціональних розладів ШКТ у дітей найбільш часто зустрічаються функціональна диспепсія (ФД) та синдром подразненого кишечника (СПК), які у багатьох випадках поєднуються між собою [1][2][3]. Серед таких причин виникнення функціональних розладів травного тракту, як дисбактеріоз, порушення імунного захисту мукозної оболонки, вісцеральна гіперчутливість, дисрегуляція впливу центральної нервової системи на моторну функцію, важливою є нераціональне харчування дитини [4][5][6]. Корекція раціону є дієвим методом профілактики і лікування не лише функціональних хвороб органів травлення, а й хронічних захворювань у майбутньому [7][8][9].…”
Section: вступunclassified